2022
DOI: 10.1183/13993003.04361-2020
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase like 2 is increased in asthma and contributes to asthmatic airway remodelling

Abstract: Airway smooth muscle cells (ASM) are fundamental to asthma pathogenesis, influencing bronchoconstriction, airway hyper-responsiveness, and airway remodelling. Extracellular matrix (ECM) can influence tissue remodelling pathways, however, to date no study has investigated the effect of ASM ECM stiffness and crosslinking on the development of asthmatic airway remodelling. We hypothesised that TGFβ activation by ASM is influenced by ECM in asthma and sought to investigate the mechanisms involved. This study combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
(83 reference statements)
4
8
0
Order By: Relevance
“…In agreement, we observed a significant reduction in TGFβ1‐induced MRTF‐A by PGE 2 . Further, the inhibition of LOXL2 has been shown to inhibit airway remodeling during asthma 52 . Complementing these findings, we observed that PGE 2 attenuates TGFβ1‐induced LOXL2, but not LOX expression.…”
Section: Discussionsupporting
confidence: 82%
“…In agreement, we observed a significant reduction in TGFβ1‐induced MRTF‐A by PGE 2 . Further, the inhibition of LOXL2 has been shown to inhibit airway remodeling during asthma 52 . Complementing these findings, we observed that PGE 2 attenuates TGFβ1‐induced LOXL2, but not LOX expression.…”
Section: Discussionsupporting
confidence: 82%
“…We found several overlapping pathways in the TGF-β1 and IL-13-treated microtissues which could explain the similarities in phenotypic changes. In both treatment conditions, upregulation in gene expression of ECM components and modifiers, as well as enrichment of pathways involved in focal adhesions and cell-ECM interactions supports the argument that the smooth muscle cells under the influence of these cytokines would play a hand in remodeling the airway matrix 24,37 .…”
Section: Discussionsupporting
confidence: 61%
“…Both treatments resulted in an enrichment of pathways associated with protein digestion and absorption, focal adhesion, and extracellular matrix (ECM)-receptor interaction, which correlates with the observed phenotypic changes in the microtissues by the smooth muscle (Figure 3C and D). Closer observation of the top DEGs in both conditions show an upregulation in the expression of matrix proteins, including a variety of collagen subfamily proteins and elastin (ELN), as well as proteins involved in matrix modifications such as matrix metalloprotease 2 (MMP2) and lysyl oxidase (LOX), which can crosslink collagen fibers 24 and is upregulated in both conditions (Supplementary Figure 6). The two treatment conditions also show an enrichment in epithelial to mesenchymal transition (EMT), the myogenesis pathway, and IL-2/STAT5 signaling (Figure 3C and D).…”
Section: Tgf-β1 and Il-13 Cause A Shift In The Transcriptomic Contrac...mentioning
confidence: 99%
“…Increased ECM stiffness is associated with crosslinking of interstitial collagen and fibronectin via action of lysyl oxidase family enzymes (EC 1.4.3.14, LOX, and EC 1.4.3.13, LOXL 1-4), other members of Cu-AOs. In support of this, an increase in LOXL2 expression in asthma has recently been shown to promote airway remodeling [7]. Thus, the mechanisms of biochemical processes underlying the development of BA can be directly related to the…”
mentioning
confidence: 90%